Penggunaan Metode Cantol Roudhoh Dalam Meningkatkan Kemampuan Membaca Anak Usia Dini Kelompok A Di RA Muslimat Nu 013 Islamiyah II Sedah - Fitri, Umu (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2020)
This study aims to determine the application of the Cntol Roudhoh method in improving reading skills in Kindergarten. The research was conducted at RAM Muslimat NU 013 Islamiyah II in Sedah Village, Jenang District, Ponorogo Regency, involving students and teachers. This research is a qualitative research with a case study research type. Data collected by observing, interviewing, then analyzing documents. The data were analyzed using qualitative data analysis techniques. The results of this study indicate the application of the cantol roudhoh method in the RAMNU 013 Islamiyah II Sedah institution, namely the teacher conveys the systematic delivery of packages, namely from the prologue, introducing cantol, lined up, calling, singing, shuffling, lining up, calling, hiding, lining up, calling, arm in arm, line up , hidden and then lined up, explaining the activities and evaluation. After that, students are allowed to come forward one by one to find out whether the students really understand or not. The effectiveness of the cantol roudhoh method at the RAMNU 013 Islamiyah II Sedah institution is very effective, seen from the children being very enthusiastic and interesting every time the teacher delivers and every graduation from the institution is certain to be able to read fluently. The advantages of the cantol roudhoh method in the RAMNU 013 Islamiyah II Sedah institution are that the average child can read quickly and easily. While the drawback is that the shortcomings of the cantol raoudhoh method are only the ineffective time used, because in the institution it is included in the learning material so that hours are very limited with the number of students in the institution